Inter-individual inequality in BMI: An analysis of Indonesian Family Life Surveys (1993–2007). (December 2016) - Vaezghasemi, Masoud; Razak, Fahad; Ng, Nawi; Subramanian, S.V.
Abstract: Widening inequalities in mean Body Mass Index (BMI) between social and economic groups are well documented. However, whether changes in mean BMI are followed by changes in dispersion (or variance) and whether these inequalities are also occurring within social groups or across individuals remain understudied. In addition, a substantial body of literature exists on the global increase in mean BMI and prevalence of overweight and obesity. However, whether this weight gain is shared proportionately across the whole spectrum of BMI distribution, also remains understudied. We examined changes in the distribution of BMI at the population level over time to understand how changes in the dispersion reflect between-group compared to within-group inequalities in weight gain. Moreover, we investigated the entire distribution of BMI to determine in which percentiles the most weight gain is occurring over time. Utilizing four waves (from 1993 to 2007) of Indonesian Family Life Surveys (IFLS), we estimated changes in the mean and the variance of BMI over time and across various socioeconomic groups based on education and households' expenditure per capita in 53, 648 men and women aged 20–50 years. An increase in mean and standard deviation was observed among men (by 4.3% and 25%, respectively) and women (by 7.3% and 20%, respectively) over time. Quantile-Quantile plots showed that higher percentiles had greater increases in BMI compared to the segment of the population at lower percentiles. While between socioeconomic group differences decreased over time, within-group differences increased and were more prominent among individuals with poor education and lower per capita expenditures. Population changes in BMI cannot be fully described by average trends or single parameters such as the mean BMI. Moreover, greater increases in within-group dispersion compared with between-group differences imply that growing inequalities are not merely driven by these socioeconomic factors at the population level. Highlights: What is already known on this subject?: Summary estimates of population change, such as mean BMI and prevalence of overweight/obesity are frequently used in population studies. Population level inequalities in weight gain are most commonly measured by between socioeconomic group differences. What this study adds?: In an Indonesian population, these summary estimates don't capture unequal changes in the BMI distribution over time. Focus on between-group differences may mask increasing inequality occurring within individuals in socioeconomic groups.